The degree of use of the Ain educational portal in distance education and the obstacles and requirements of use from the point of view of teachers and primary school principals in the city of Abha - Al-Qahtani, Manal Ali Al Saad (Journal of Educational and Psychological Sciences, 2023)
The study aimed to reveal the degree of use of Ain Educational Portal in distance education in education from the point of view of teachers and school principals in the city of Abha, and to achieve the objectives of the study, the descriptive analytical approach was used. The study tool was a questionnaire to collect data and information, which was applied to a sample of (49) teachers, administrators and managers in the city of Abha in the Kingdom of Saudi Arabia.. The results showed that the degree of use of the Ain educational portal in distance education in the primary stage from the point of view of teachers and primary school principals in the city of Abha is very high, as it came with an average of 6.29, and that the level of obstacles to the use of the Ain educational portal in distance education in the primary stage from the point of view of teachers and primary school principals in the city of Abha is very high, as it came with an average of 6.32. The results also showed that the level of requirements that must be met to activate the role of the Ain Educational Portal in distance education from the point of view of teachers and primary school principals in the city of Abha is very high, with an average of 611.
Keywords: Degree of use; e-learning; distance education; Ain Educational Portal; Abha